Peran Teknologi Dalam Mendukung Respons Terhadap Kegawatdaruratan K3 di Industri - Karina Nasution, Priska; Hasibuan, Abdurrozzaq; Aulia, Shabina; Puspa Dewi, Virda (PT. Alahyan Publisher Sukabumi, 2024)
Information technology has become the backbone of various industrial sectors and its role in improving occupational health and safety emergency preparedness cannot be underestimated. Information technology has changed the way we work, manage and respond to emergencies in industrial environments, including in the context of industrial technology which often involves complex and potentially high-risk operations. This study aims to analyze the role of technology in supporting the response to k3 emergencies in the industry. The research method used is literature research or literature study to obtain research data and use a qualitative approach produced in the form of words or descriptive from books, and journals related to the role of technology in supporting responses to k3 emergencies in industry. The results explain that visualization technology that can be done during work is used as safety training, which combines Building Information Modeling (BIM) and Virtual Reality (VR) technology to create situations in the work environment such as field situations that are created and employees are easy for them to identify risks that may be faced during work. It can be concluded that information technology has an important function in improving occupational health and safety emergency preparedness in the technology industry. The use of information technology has great potential to create a work environment that is safer, responsive, and ready to face health and safety challenges in the technology industry.